2021
DOI: 10.1088/1402-4896/ac3046
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric doping induced nonlinear electron mobility in double V-shaped quantum well based FET structure under external electric field

Abstract: The effect of asymmetric doping profile on the electron mobility μ is studied in a Field Effect Transistor (FET) structure based on Al x Ga 1−x As double V-shaped quantum well (D-VQW) in presence of an external electric field F. We introduce asymmetry in the structure by considering different doping concentrations in the side barriers along the substrate and surface. The resultant asymmetric potential is varied as a function of F. Accordingly the energy levels E l and wave functions ξ l within the coupled stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The resultant potential can be manipulated by varying doping concentration (N d ). Several studies have been reported to improve the transport and optical properties of NSQW structures by amending the resultant potential in terms of N d [16,20,[26][27][28]. The effect of doping on μ for different double NSQW and asymmetric PQW structures has been reported [16,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant potential can be manipulated by varying doping concentration (N d ). Several studies have been reported to improve the transport and optical properties of NSQW structures by amending the resultant potential in terms of N d [16,20,[26][27][28]. The effect of doping on μ for different double NSQW and asymmetric PQW structures has been reported [16,20].…”
Section: Introductionmentioning
confidence: 99%
“…Dakhlaoui enhanced the optical properties such as intersubband transition and optical absorption coefficient in step quantum well structure by considering δ-doping in different layers of the well [26]. Jena et al obtained oscillatory μ mediated by the applied electric field in an asymmetric double V-shaped QW (VQW) structure [28].…”
Section: Introductionmentioning
confidence: 99%